ADAPTASI WARNA BURUNG JULANG SULAWESI PADA BUSANA PESTA SIANG DENGAN HIASAN ANYAMAN DAN MERONCE - Chane Florentia Aileen; Cucu Ruhidawati (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2022)
The Knobbed Hornbill is one of Indonesian endemic animal who lives in Sulawesi Island. This bird only exist in one island, indirectly effected to very few population of Knobbed Hornbill and vulnerable to extinction. By that condition, Knobbed Hornbill must be preserved and introduced it to Indonesian society. The qualitative method applied in this research is Knobbed Hornbill literature study, visual analysis, and experiment to make strings of beads also modified the base shape of braiding. The result of this research will be applied to semi formal women daytime party dress. This outfit will visualized the color, shape, and habits of Knobbed Hornbill. Braiding and string of beads will be used as intermediary media to explain the point of the product. The aims of this research is to spread awareness of Indonesia endemic animal which is Knobbed Hornbill, and prevent this bird to extinct .